Climate-Smart Agriculture across scales in Latin America - Loboguerrero Rodriguez, Ana María; Martínez Barón, Deissy (2017)
Manuscript - The implementation of climate-smart agriculture (CSA) in Latin America presents interesting challenges and opportunities, especially when considering the region’s agrobiodiversity, natural resources, and socioeconomic and cultural contexts.